2020
DOI: 10.20473/fmi.v55i4.17309
|View full text |Cite
|
Sign up to set email alerts
|

Effect of In-Vitro Alpha Lipoic Acid Addition on Spermatozoa Motility in Sperm Preparation Process

Abstract: Infertility is a problem for husband and wife, in the last 20 years the number of infertile couples has tended to increase by around 6.5 million pairs. The infertile couple can use the intrauterine insemination method to obtain offspring if a conventional method approach cannot be performed. Insemination requires a sperm preparation stage in which there are centrifugation and resuspension procedures that tend to produce excess reactive oxygen species (ROS). Excessive ROS will damage the motility of the spermat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Exogenous ALA supplementation has been reported to increase unbound ALA levels, which can act as a potent antioxidant and reduce oxidative stress both in vitro and in vivo (Canepa et al, 2018;Haghighian et al, 2015;Yeni et al, 2012). A previous study reported that the addition of ALA in sperm preparation could improve the sperm motility and vitality as well as the total motile sperm count (TMSC) (Buanayuda, Lunardhi, & Mansur, 2019). ALA supplementation in the swim up and density gradient centrifugation can select sperm with lower DNA fragmentation (Lestari, Lestari, & Pujianto, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous ALA supplementation has been reported to increase unbound ALA levels, which can act as a potent antioxidant and reduce oxidative stress both in vitro and in vivo (Canepa et al, 2018;Haghighian et al, 2015;Yeni et al, 2012). A previous study reported that the addition of ALA in sperm preparation could improve the sperm motility and vitality as well as the total motile sperm count (TMSC) (Buanayuda, Lunardhi, & Mansur, 2019). ALA supplementation in the swim up and density gradient centrifugation can select sperm with lower DNA fragmentation (Lestari, Lestari, & Pujianto, 2018).…”
Section: Introductionmentioning
confidence: 99%